Selecting "App" ealing and "App" ropriate Book Apps for Beginning Readers. (23rd August 2013) - Cahill, Maria; McGill‐Franzen, Anne
Abstract: Beginning with a brief rationale for selecting quality digital picture book apps for beginning readers, the authors describe the elements of digital picture books and provide a brief review of the instructional benefits of digital picture book use for beginning readers. They then present a detailed taxonomy for selecting quality picture book apps. Examples drawn from actual apps available for young children illustrate the concepts addressed. Beginning with a brief rationale for selecting quality digital picture book apps for beginning readers, the authors describe the elements of digital picture books and provide a brief review of the instructional benefits of digital picture book use for beginning readers. They then present a detailed taxonomy for selecting quality picture book apps. Examples drawn from actual apps available for young children illustrate the concepts addressed.